Physicochemical and sensory parameters correlation as a tool to establish the varietal aptitude of minimally processed peaches treated with gamma irradiation - Colletti, Analia Cecilia; Soteras, Trinidad; Pieroni, Victoria; Budde, Claudio Olaf; Pachado, José A.; Vaudagna, Sergio Ramon; Polenta, Gustavo Alberto; Denoya, Gabriela Inés (Elservier, 2025)
Demand for minimally processed fruit and vegetables is rising as consumers seek fresh, nutritious options year-round. Irradiation technology, a non-thermal phytosanitary method, can improve texture, antioxidant capacity, inhibit browning-related enzymes and promote physiological metabolism in fruit without compromising quality. However, postharvest behavior and physiological responses vary across cultivars. A comprehensive study was conducted to characterize the aptitude of peach varieties (Prunus persica L. Batsch cv. Flordaking, Early Grand, Dixiland and Fayette) to minimal processing and gamma irradiation (0.2 kGy). Changes in color, organic acids, sugars, firmness and sensory descriptors of appearance, odor, taste, flavor and mouthfeel were assessed using a trained sensory panel. Irradiation effectively preserved the physicochemical quality properties and enhanced various sensory attributes associated with fruit ripening. PLS regression analysis reveals that cv. Flordaking and Early Grand presented higher values of firmness, h° and ascorbic acid content, and were perceived as having greater hardness, a crunchy texture, a green odor and flavor, and an acidic and bitter taste. In contrast, cv. Dixiland and Fayette showed typical characteristics of ripe fruit with attributes, such as juiciness and peach flavor and odor. In particular, irradiated samples of cv. Dixiland showed a higher positive correlation with C *, glucose and fructose content, and perception of sweet taste, brightness and peach flavor. The study concludes that cv. Dixiland would be the most appropriate variety for minimal processing and the application of gamma irradiation. These reports suggest that multiple correlation analyses between physicochemical and sensory parameters could determine varietal aptitude for postharvest technologies and predict consumer preferences, contributing to the production of high-quality fruit products. //Resumen: La demanda de frutas y verduras mínimamente procesadas está aumentando, ya que los consumidores buscan opciones frescas y nutritivas durante todo el año. La tecnología de irradiación, un método fitosanitario no térmico, puede mejorar la textura, la capacidad antioxidante, inhibir las enzimas relacionadas con el pardeamiento y promover el metabolismo fisiológico en la fruta sin comprometer la calidad. Sin embargo, el comportamiento poscosecha y las respuestas fisiológicas varían según el cultivar.